Фінансове забезпечення соціальної сфери в Україні - Попов, В. М.; Неревська, К. І.; Popov, V.; Nerevckaiy, K. (КНТУ, 2013)
В статті проаналізовано сучасний стан фінансування соціальної сфери в Україні та його вплив на забезпечення населення соціальними послугами на достатньому рівні та належної якості, розроблено пропозиції щодо підвищення ефективності функціонування соціально-культурних галузей з урахуванням фінансових аспектів їх розвитку. The aim of the paper is summarized and deepen the theoretical base for social sphere and rationale set of recommendations for improving the efficiency of its operation based on the financial aspects of development. This paper analyzes the current state of funding social services in Ukraine and its impact on provision of social services at a sufficient level and of good quality. Definitely, now Ukraine in terms of financing social sector remains far behind the developed countries. Funds are lacking not only in the field of social development sector, but also in their routine maintenance that lead to the decline of social and cultural facilities, poor provision of services and the system of social protection and social character of existing programs are not effective in reducing level or poverty in Ukraine. Therefore there is a need for new approaches and develop an effective financing mechanism for effective social sphere. In the article the proposals to improve the functioning of the socio-cultural sectors including the financial aspects of their development.
Financing of social services in Ukraine
Keywords: соціальна сфера; соціальна інфраструктура; бюджетні кошти; соціальні інвестиції; медичне страхування; кредитні ресурси